Effects of Different Amine Activators on the Monomer Conversion, Biaxial Flexural Strength, and Color Stability of Experimental Provisional Dental Restorations - Padunglappisit, Chawal; Posaya-anuwat, Siwanath; Sompoch, Varisara; Piyawiwattanakoon, Poompat; Panpisut, Piyaphong (European Journal of Dentistry, 2021)
Objective The aim was to assess the effect of different amine activators including N, N-dimethyl-p-toluidine (DMPT) or Na-N-tolyglycine glycidyl methacrylate (NTGGMA) on chemical-activated monomer conversion, biaxial flexural strength (BFS), and color stability of composites for provisional dental restorations.Materials and Methods Two formulations of composites containing either DMPT (D-temp) or NTGGMA (N-temp) were prepared. The degree of monomer conversion was assessed. The BFS of the materials was tested using the ball-on-ring testing jig. The color difference (∆E00) of the materials after immersion in water was also determined. The commercial comparisons were Unifast (UF), Protemp (PT), Luxacrown, and Luxatemp (LT).Results The monomer conversion of D-temp (57.4 ± 1.3%) was comparable to that of N-temp (59.0 ± 1.3%). The conversion of both D-temp and N-temp were higher than that of PT (48.1 ± 3.4%) and LT (48.0 ± 1.6%). BFS of both D-temp (164.2 ± 18.1 MPa) and N-temp (168.6 ± 8.9 MPa) were comparable but higher than that of UF (119.8 ± 13.6 MPa). ∆E00 of D-temp (2.7 ± 0.7) and N-temp (2.5 ± 0.8) were comparable but higher than that of other commercial materials (0.6–1.2).Conclusion The use of DMPT or NTGGMA showed negligible effect on monomer conversion, BFS, and color stability of the experimental provisional restorations. The conversion and BFS of the experimental materials were in the range of that obtained from commercial bis-acryl-based materials. However, the color stability of the experimental materials was lower than that of commercial materials.
Keywords: composite resin; temporary; polymerization; flexural strength; color stability